Ocean grabbing. (July 2015) - Bennett, Nathan James; Govan, Hugh; Satterfield, Terre
Abstract: The term "ocean grabbing" has been used to describe actions, policies or initiatives that deprive small-scale fishers of resources, dispossess vulnerable populations of coastal lands, and/or undermine historical access to areas of the sea. Rights and access to marine resources and spaces are frequently reallocated through government or private sector initiatives to achieve conservation, management or development objectives with a variety of outcomes for different sectors of society. This paper provides a definition and gives examples of reallocations of marine resources or spaces that might constitute "ocean grabbing". It offers a tentative framework for evaluating whether marine conservation, management or development is ocean grabbing and proposes an agenda for future research. For a reallocation to be considered ocean grabbing, it must: (1) occur by means of inadequate governance, and (2) be implemented using actions that undermine human security and livelihoods, or (3) produce impacts that reduce social–ecological well-being. Future research on ocean grabbing will: document case studies, drivers and consequences; conduct spatial and historical analyses; and investigate solutions. The intent is to stimulate rigorous discussion and promote systematic inquiry into the phenomenon of ocean grabbing. Highlights: Ocean grabbing refers to acts of dispossession or appropriation of marine resources or spaces. Ocean grabbing robs fishers and communities of use, control or access to resources, land or the sea. This paper presents a framework to evaluate conservation or development initiatives for ocean grabbing. Three factors, governance, human security and well-being, determine what constitutes ocean grabbing. A systematic program of research into the phenomenon of ocean grabbing is proposed.